1996
DOI: 10.1042/bj3190749
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-transferase class Kappa: characterization by the cloning of rat mitochondrial GST and identification of a human homologue

Abstract: We have isolated a cDNA clone that encodes rat glutahione S-transferase (GST) subunit 13, a GST originally isolated from rat liver mitochondrial matrix by Harris, Meyer, Coles and Ketterer [(1991) Biochem. J. 278, 137-141]. The 896 bp cDNA contains an open reading frame of 678 bp encoding a deduced protein sequence of which the first 33 residues (excluding the initiation methionine residue) correspond to the N-terminal sequence reported by Harris et al. Hence like many other nuclear-encoded, mitochondrially lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
171
0
3

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(177 citation statements)
references
References 24 publications
3
171
0
3
Order By: Relevance
“…Subsequently, a human cDNA was identified that exhibited a high level of identity with rGSTK1 (9). However, the hGSTK1 gene and protein have not been extensively characterized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, a human cDNA was identified that exhibited a high level of identity with rGSTK1 (9). However, the hGSTK1 gene and protein have not been extensively characterized.…”
Section: Discussionmentioning
confidence: 99%
“…In 1991, Harris et al (18) reported the purification of a GST isolated from mitochondrial matrix of rat liver, GST13-13. Although this subunit was initially classified as a class Theta GST on the basis of N-terminal analysis, elucidation of its complete amino acid sequence by Pemble et al (9) showed the absence of sequence similarity to any other class of GST. Pemble et al also identified human sequences in expressed sequence tag database that showed a high nucleotide similarity (77%) to that of rat GST subunit 13.…”
mentioning
confidence: 99%
“…Cytosolic mammalian GSTs can be classified, based on amino acid sequences, into at least eight distinct classes: alpha, mu, pi (9,10), theta (11,12), sigma (13,14), kappa (15), zeta (16), and omega (17). The sequence identities between any two members within a class are typically greater than 70% and usually less than 30% between classes (1,7,8).…”
mentioning
confidence: 99%
“…Hepatocytes express microsomal GSTs on their plasma membranes that are 17.2 kDa in molecular mass [6]. Mammalian GSTs can be grouped into at least seven classes namely K, W, Z, c, a (the cytosolic forms) [5], the U (the mitochondrial form) [7] and the microsomal form [5].…”
Section: Introductionmentioning
confidence: 99%